Estudo da filogenia dos anofelinos brasileiros do subgênero Nyssorhynchus e padronização da amplificação dos genes do receptor do peptídeo sexual (SPR) e do peptídeo sexual (SP) - Oda, Letícia Tiemi Egami [UNESP] (2014)
The evolution of mosquitoes hematophagy is undoubtedly the most important adaptation of this group of insect in terms of pathogens transmission, which cause various important diseases in the world nowadays. Thus, a common misconception that mosquitoes as a group are known taxonomically was generated, but there are many species to be discovered and classified. The mosquitoes of Culicidae Family which has Anophelinae as subfamily are a diverse group of monophyletic origin, with global distribution. It is noteworth that only a minority of the 3200 species known today, are important vectors of pathogens to humans. Besides the pathogens transmission, mosquitoes have much to offer to basic science, for example, as biodiversity indicators, indicating also the degradation degree of the natural environment, the various ways soil is explored and for studies of evolution and speciation. The mosquitoes have a peptide called Sex Peptide which is expressed in accessory glands of males and is inseminated in females during copulation. The binding of this peptide to its receptor triggers a major behavioral response in the insects, which includes changes in eating habits, giving preference to protein, the refusal of mating with other males, induction of oviposition, among others. This project aims the study of this peptide and its corresponding receptor in different brasilian anophelines in order to generate data about phylogeny and characterization of a possible genetic marker. DNA extraction were made, PRC reaction, sequencing, and sequence analysis for tree generation in the program Phylip whith the anylisis of Maximum Likelihood,Neighbor- Joining and Parsimony.The generated tree was compared whith a standard tree of Foste et al (2013) which used three diferent genes COI, CAD e white gene. We didn´t get successful whith SPR tree, but, with SP the classification of the tree were almost the same of Foster et al (2013). Another tree was generated whith ...